Vintage Viewing Bruhn, Nureyev and Excelsior on DVD reviewed - Robertson, Allen (Dance Books Ltd., Alton,Hampshire (UK), 2003)
Review of Bruhn, Nureyev and Excelsior on DVD . PALABRAS CLAVE: Erik Bruhn, Rudolf Nureyev, Excelsior.
Rudolf Nureyev and Erik Bruhn: The Complete Bell Telephone Hour Performances. Video Artists International. Excelsior. Luigi Manzotti. Orchesta & Corps de Ballet of the Teatro Alla Scala. TDK mediaactive.